Multi-mode Motion Analysis of Sideward Opening Aircraft Doors Based on Position and Orientation Characteristic Theory - Wu Borui; Hang Lubin; Peng Jiyou; Huang Xiaobo; Wu Yang; Qiu Xudong (Jixie chuandong)
As an important part of large passenger aircraft, the analysis of motion state and motion mode of passenger doors is very important for the design of door function and motion mechanism. From the viewpoint of topological synthesis of robot mechanism, it is proposed for the first time to abstract the opening motion mechanism of a certain type of the sideward opening aircraft door into a parallel mechanism composed of two SS branches and one <alternatives>◇(R//R//R//R)⊥R//R <?fx-imagestate width="33.35866928" height="3.47133350"?> <?fx-imagestate width="33.35866928" height="3.47133350"?> </alternatives> branch, and research on the overall motion correlation of the sideward opening aircraft door and its opening mechanism is conducted. Based on the position and orientation characteristic (POC) theory, the topological dimension constraint type characteristics of the sideward opening aircraft door mechanism is analyzed. It reveals that the door mechanism possesses two kinds of motion modes with one degree of freedom and different number of non-independent elements during the lifting and rotating processes. The study finds that the geometric constraint condition of the sideward opening aircraft door motion mode switching is that the rotation pair spacing of hinge arm mechanism is equal to the projection size of the parallel link mechanism length on the horizontal plane. The aircraft door drive combined with limiting stopper ensures the constant geometric constraint conditions, improves the accuracy of door mode switching and the stability of the opening process. Research on the opening process of the sideward opening aircraft door based on POC theory provides a new idea for aircraft door design.